Digitalisation, energy and data demand: The impact of Internet traffic on overall and peak electricity consumption. (April 2018) - Morley, Janine; Widdicks, Kelly; Hazas, Mike
Abstract: Over the last decade, concerns have been raised about increases in the electricity used by information technologies, other consumer electronic devices, data centres, and to a much lesser degree, Internet distribution networks. At the same time, 'smart' innovations are widely anticipated to help reduce energy demand across diverse sectors of society. Yet such potential savings, as well as the increasing use of other digital services, are predicated upon continued expansion of digital infrastructures. This paper focuses on the phenomenal growth in Internet traffic, as a trend with important implications for energy demand. It outlines an agenda to better understand how data demand is changing. Drawing on findings from our own research in combination with secondary data analysis, we examine the alignment of peak demand for electricity and data. Peaks in data appear to fall later in the evening, reflecting the use of online entertainment, but this is far from fixed. Overall, the paper argues that a better understanding of how everyday practices are shifting, in concert with the provision and design of online services, could provide a basis for the policies and initiatives needed to mitigate the most problematic projections of Internet energy use.